2015
DOI: 10.1002/mabi.201500005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Molecular Weight and Charge of Antibiotics on Their Release Kinetics From Gelatin Nanospheres

Abstract: In this study, we investigated the fundamental relationship between the physicochemical characteristics of antibiotics and the kinetics of their release from gelatin nanospheres. We observed that antibiotics of high molecular weight (colistin and vancomycin) were released in a sustained manner from oppositely charged gelatin carriers for more than 14 d, as opposed to antibiotics of low molecular weight (gentamicin and moxifloxacin) which were released in a burst-like manner. The release kinetics of positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
(50 reference statements)
5
25
0
Order By: Relevance
“…Moreover, in vivo investigations have shown that these materials can be used as osteoconductive bone fillers with in vivo drug release ability . Although the assembly of biomaterials from colloidal particles was shown to be a promising strategy for the development of injectable and self‐healing gels with tissue regenerative[8a,b,9b,c,20] and drug release[9a,21,22] capabilities, the potential of colloidal gel systems for regeneration of osteoporotic bone defects has never been explored before. Hence, the goal of this study was to develop injectable and self‐healing composite colloidal gels that combine mechanical robustness with the capacity to regenerate osteoporotic bone through the concerted action of anabolic and anticatabolic stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in vivo investigations have shown that these materials can be used as osteoconductive bone fillers with in vivo drug release ability . Although the assembly of biomaterials from colloidal particles was shown to be a promising strategy for the development of injectable and self‐healing gels with tissue regenerative[8a,b,9b,c,20] and drug release[9a,21,22] capabilities, the potential of colloidal gel systems for regeneration of osteoporotic bone defects has never been explored before. Hence, the goal of this study was to develop injectable and self‐healing composite colloidal gels that combine mechanical robustness with the capacity to regenerate osteoporotic bone through the concerted action of anabolic and anticatabolic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…These gels are solely composed of colloidal particles. Various types of particles can be used as colloidal building blocks, which can be loaded or functionalized with different types of drugs or biomolecules . By utilizing reversible, noncovalent interparticle bonds, self‐healing colloidal gels can be prepared that recover their mechanical properties after destructive shearing upon extrusion through needles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[81b] The particle size of these colloidal gels strongly influenced the functional properties of resulting colloidal gels as gels made of gelatin microspheres were less elastic, less cohesive, less injectable and non‐self‐healing, as opposed to colloidal gels prepared from gelatin nanoparticles . In vitro investigations showed that the nanostructured gelatin‐based colloidal gels facilitated controlled release of multiple growth factors as well as antibiotics . In vivo investigations revealed that these colloidal gelatin gels allowed controlled delivery of angiogenic basic fibroblast growth factor and osteogenic bone morphogenetic protein‐2 for the regeneration of bone defects.…”
Section: Intrinsic Self‐healing Biomaterialsmentioning
confidence: 99%